Pengaruh Kualitas Interaksi Atasan–Bawahan Dan Politik Organisasi Terhadap Organizational Citizenship Behavior Pada Pegawai Negeri Sipil Pemerintah Kota Solok - Dyanisa, Tifanny; Zulkarnain, Zulkarnain; Zahreni, Siti (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
This study aims to determine the influence of leader-member exchange and organizational politics toward organizational citizenship behavior. The result showed that receiving Leader-member exchange positively affects to organizational citizenship behavior and organizational politics negatively affects to organizational citizenship behavior. This research indicates the importance of leader-member exchange and organizational politic toward organizational citizenship behavior.